Muslims’ willingness to pay for certified halal food: an extension of the theory of planned behaviour - Iranmanesh, Mohammad; Mirzaei, Maryam; Parvin Hosseini, Seyed Mehrshad; Zailani, Suhaiza (Emerald, 2019)
Purpose: The purpose of this paper is to extent the theory of planned behaviour (TPB), when extended by self-identity and religious commitment (RC), and is able to predict Muslim consumers’ willingness to pay (WP) for certified halal food. Design/methodology/approach: A survey of 277 Muslim consumers in Malaysia was conducted and the cross-sectional data were analysed using the partial least squares technique. Findings: Attitude (ATT) and religious self-identity (RSI) were found to have a positive impact on WP for certified halal food. Additionally, RC has a positive effect on ATT and RSI and has a positive moderating effect on the relationship between perceived behavioural control and WP. Practical implications: The findings can benefit halal food companies by offering an insight into the willingness of Muslim consumers to pay for certified halal food. Originality/value: The findings contribute to the research on halal foods by illustrating the factors that determine Muslim consumers’ WP for certified halal food. This study also extends the understanding of the TPB to the halal food context. © 2019, Emerald Publishing Limited.